Trauma-Informed School Counseling for Internally Displaced Students in Conflict-Affected Regions - David K. Mensah (Mauve Journal De Leardu, 2026)
This study examines the implementation of trauma-informed school counseling for internally displaced students in conflict-affected regions. The research aims to analyze how trauma-informed counseling practices support students’ psychosocial recovery, emotional resilience, and educational participation within fragile educational environments. Using a qualitative multiple case study approach, data were collected through semi-structured interviews, observations, and document analysis involving counselors, teachers, school administrators, humanitarian officers, and internally displaced students from selected conflict-affected schools. The findings indicate that displacement-related trauma significantly influences students’ emotional well-being, classroom behavior, social interaction, and academic engagement. Trauma-informed counseling practices emphasizing emotional safety, empathy, trust-building, and collaborative psychosocial support contributed positively to students’ resilience, peer connectedness, and educational continuity. However, the implementation process was constrained by institutional limitations such as counselor shortages, inadequate professional training, limited psychosocial resources, and weak policy support. The study implies that trauma-informed approaches should become central components of educational policy and humanitarian schooling strategies for displaced learners in conflict-affected regions.